STUDY ON THE NEEDS AND WILLINGNESS TO PAY FOR COLORECTAL CANCER SCREENING AMONG RESIDENTS IN SOME WARDS OF HUE CITY (Vietnam Journal of Community Medicine, 2026)
Colorectal cancer (CRC) screening is recommended as an effective strategy to reduce morbidity and mortality. The study aimed to examine the need for CRC screening and to identify willingness to pay (WTP) for such services and some related factors in Hue City. A cross-sectional study was conducted among 420 individuals aged 45 to 75 years. WTP for colorectal cancer screening was elicited using the contingent valuation method, combining the double-bounded dichotomous choice technique with an open-ended question. Non-parametric tests were used to determine factors related to WTP. The results showed that 75.2% of participants expressed a need for CRC screening. Average WTP value for faecal occult blood testing was 258,759.5 VND (SD: 418,220.7) and for colonoscopy was 1,339,288.0 VND (SD: 1,130,341.0). Education level, physical activity, family history of CRC and having heard of CRC were found to be significantly associated with WTP. The findings indicate a demand for CRC screening among the study population. Strengthening health communication and promoting the implementation of effective CRC screening programs are recommended.
Keywords: screening needs, willingness to pay, colorectal cancer, Hue City.